PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT TERANG DUNIA INTERNUSA TANGERANG SELATAN - Reza Kurniawan, Mohamad; Azis, Abdul (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of leadership and motivation on employee performance at PT. The Light of the Internusa World in South Tangerang. The method used is quantitative. The sampling technique used the slovin formula and obtained a sample of 109 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that leadership has a significant effect on employee performance with a determination coefficient value of 41.8% and the hypothesis test is obtained t count > t table or (8.765 > 1.982). Motivation has a significant effect on employee performance with a coefficient of determination of 39.9% and the hypothesis test is obtained t count > t table or (8.421 > 1.982). Leadership and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 9.218 + 0.394X1 + 0.383X2. The coefficient of determination is 39.9% while the remaining 60.1% is influenced by other factors. Hypothesis testing obtained F count > F table or (58.645 > 2.690).